Sport psychology essentials - Collins, Dave (Sports psychologist); Cruickshank, Andrew (Sports psychologist)
This comprehensive look at sport psychology presents current research-based information and applied techniques to benefit coaches, athletes, performance specialists, and sport psychology consultants. Topics include making sport psychology work, strengthening athletes' performance mindset, and enhancing team performance potential. Special emphasis is placed on developing confidence, increasing motivation, and preparing individuals and teams for optimal performance"--Provided by publisher.
Blending mental training into a performance program / Dave Collins and Andrew Cruickshank -- Case conceptualization : strategies for assessing and conceiving / Amanda Martindale -- Integrating athlete- and performance-centered approaches / Andreas Ku?ttel -- Putting into practice sound philosophical approaches to sport psychology / Artur Poczwardowski -- Motivation / David Shearer -- Confidence / Denis Hauw -- Imagery and mental practice / Geoff P. Lovell and John K. Parker -- Self-regulation / Tynke Toering -- Concentration, focus, and attention / John Toner -- Reflection and balance / Carlos Eduardo Gonc?alves and Humberto Moreira Carvalho -- Leadership / Andrew Cruickshank -- High-performing cultures / Geir Jordet and Rune Giske -- Shared mental models / Pam Richards and Dave Collins -- Macrostructures and microsystems / Dave Collins -- Program integration / Tom Willmott -- Motoric considerations / Maurizio Bertollo and Antonio De Fano -- Talent development / A?ine MacNamara -- Practice and transfer to competition, peaking, and performing / Boris Blumenstein and Iris Orbach -- Countering slumps and adversity / Andreas Stenling and Andreas Ivarsson -- Epilogue : getting help : what to look for and what to expect in a consultant / Andrew Cruickshank and David Collins.
Ms. Camia (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Sports -- Psychological aspects; Athletes -- Psychology